2019
DOI: 10.1016/j.jot.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in diagnosis of osteoporosis by quantitative computed tomography and dual-energy X-ray absorptiometry in Chinese elderly men

Abstract: Objective The objective of this study was to investigate the diagnostic discordance of osteoporosis by quantitative computed tomography (QCT) and dual-energy X-ray absorptiometry (DXA) in Chinese elderly men. Methods A total of 313 males older than 60 years, who underwent both spinal QCT and lumbar spine and hip DXA in our department, were included. The diagnostic criteria established by the World Health Organisation in 1994 were used for DXA to diagnose osteoporosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…DXA remains the gold standard for the diagnosis of OP; however, although DXA is widely available, its detection performance is relatively limited. The previous study of our hospital found that QCT had a higher OP detection rate than did DXA (12).…”
Section: Introductionmentioning
confidence: 62%
“…DXA remains the gold standard for the diagnosis of OP; however, although DXA is widely available, its detection performance is relatively limited. The previous study of our hospital found that QCT had a higher OP detection rate than did DXA (12).…”
Section: Introductionmentioning
confidence: 62%
“…33 Additionally, a recent research also found NF-κB (p65) is a key transcription factor that acts as a crucial modulator in cell growth cell apoptosis and tumorigenesis. 34 Furthermore, suppression of migration and invasion was found once NF-κB pathway was inactivated, 35 which is a key step in mediation of MMP transcription. Our research first found nobiletin could increase the level of NF-κB in the nuclei of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…DXA cannot distinguish between cortical bone and trabecular bone, and it is sensitive to the presence of aortic calcifications, vertebral fracture, spine degeneration such as vertebral osteophytes, end-plate sclerosis, facet joint degeneration, and ligament calcification, which can all lead to falsely increased lumbar vertebral areal BMD (aBMD) [ 39 ]. Although DXA is a well-established technique, QCT is a more accurate method for BMD assessment and a more sensitive modality for the evaluation of BMD changes [ 7 , 40 ]. Xu et al found that the detection rate of osteoporosis in men older than 60 years was significantly higher by QCT than by DXA [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although DXA is a well-established technique, QCT is a more accurate method for BMD assessment and a more sensitive modality for the evaluation of BMD changes [ 7 , 40 ]. Xu et al found that the detection rate of osteoporosis in men older than 60 years was significantly higher by QCT than by DXA [ 7 ]. Where aBMD measured by DXA includes both cortical and trabecular bone, vBMD derived from QCT is focused on a volumetric measure of vertebral trabecular bone that has a high turnover rate compared to cortical bone [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation